The influence of family support during endoscopic submucosal dissection on patient's anxiety - Gao, Ruo-Yu; Gan, Ri-Yun; Huang, Jia-Lan; Liu, Ting-Ting; Wu, Ben-Hua; Wang, Li-Sheng; Li, De-Feng; Yao, Jun (Frontiers in Public Health, 2022)
Background Psychological problems may promote peptic ulcers. Ulcer-like wounds can be formed after gastric endoscopic submucosal dissection (ESD). The influence of family support on the healing of gastric ESD-induced ulcers remains largely undetermined. Objective In the present study, we aimed to assess the Hospital Anxiety and Depression Scale (HADS) scores and the incidence of post-ESD complications in patients with family support in the care process and those in the non-relative group. Materials and methods A total of 191 patients aged between 30 and 70 years who received gastric ESD were evaluated with the Chinese version of HADS. Differences in depression and anxiety between the two groups were compared using the chi-square test and t-test. Multivariable logistic regression models were used to examine whether anxiety and depression were the risk factors for post-ESD complications. Results The mean values of HADS-A (4.61 ± 2.89 vs. 5.56 ± 3.07, p = 0.042) and HADS-D (4.14 ± 3.03 vs. 4.97 ± 2.61, p = 0.048) scores were significantly lower in patients with accompanying relatives compared with those in the non-relative group. Besides, through the pre-ESD and post-ESD self-contrast, the scores of anxiety and depression in the relative-group were 0.57 and 0.56, respectively (p < 0.001), while those in the non-relative group were increased by 1.43 and 1.49, respectively (p < 0.001). Multivariable logistic regression analysis revealed that HADS-A, HADS-D scores, and age were significantly correlated with post-ESD abdominal pain (P < 0.05). Conclusions The occurrence and degree of adverse emotions such as psychological anxiety and depression in patients who received gastric ESD with accompanying relatives during hospitalization may were reduced, and the incidence of gastric post-ESD abdominal pain may was also decreased.